The myth of nations the Medieval origins of Europe - Geary, Patrick J. (Princeton Princeton University Press, 2002)
Modern-day Europeans by the millions proudly trace back their national identities to the Celts, Franks, Gauls, Goths, Huns, or Serbs--or some combination of the various peoples who inhabited, traversed, or pillaged their continent more than a thousand years ago. According to Patrick Geary, this is historical nonsense. The idea that national character is fixed for all time in a simpler, distant past is groundless, he argues in this unflinching reconsideration of European nationhood. Few of the peoples that many Europeans honor as sharing their sense of ''nation'' had comparably homogeneous identities; even the Huns, he points out, were firmly united only under Attila's ten-year reign.
Includes bibliographical references (p. 185-187) and index.
Keywords: Nationalism--Europe--History--19th century